Links Between Testosterone, Oestrogen, and the Growth Hormone/Insulin-Like Growth Factor Axis and Resistance Exercise Muscle Adaptations - Gharahdaghi, Nima; Phillips, Bethan E.; Szewczyk, Nathaniel J.; Smith, Ken; Wilkinson, Daniel J.; Atherton, Philip J. (Frontiers in Physiology, 2021)
Maintenance of skeletal muscle mass throughout the life course is key for the regulation of health, with physical activity a critical component of this, in part, due to its influence upon key hormones such as testosterone, oestrogen, growth hormone (GH) and insulin-like growth factor (IGF). Despite the importance of these hormones for the regulation of skeletal muscle mass in response to different types of exercise, their interaction with the processes controlling muscle mass remain unclear. This review presents evidence on the importance of these hormones in the regulation of skeletal muscle mass and their responses, and involvement in muscle adaptation to resistance exercise. Highlighting the key role testosterone plays as a primary anabolic hormone in muscle adaptation following exercise training, through its interaction with anabolic signalling pathways and other hormones via the androgen receptor (AR), this review also describes the potential importance of fluctuations in other hormones such as GH and IGF-1 in concert with dietary amino acid availability; and the role of oestrogen, under the influence of the menstrual cycle and menopause, being especially important in adaptive exercise responses in women. Finally, the downstream mechanisms by which these hormones impact regulation of muscle protein turnover (synthesis and breakdown), and thus muscle mass are discussed. Advances in our understanding of hormones that impact protein turnover throughout life offers great relevance, not just for athletes, but also for the general and clinical populations alike.